The Effect of Flipped Classroom Model To the Reading Comprehension Seventh Grade Students at SMP Negeri 2 Siantar in A Narrative Text - Siahaan, Sanggam; Simanjuntak, Yeni Lestari; Sinurat, Bloner (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
This study aimed to examine the impact of the Flipped Classroom teaching model on the reading comprehension of seventh-grade students at SMP Negeri 2 Siantar. The Flipped Classroom is an innovative teaching approach where students engage with learning materials, such as videos, outside of class, allowing class time to be used for interactive activities, discussions, and deeper learning. The research focused on students' comprehension of narrative texts, comparing the performance of an experimental group (using the Flipped Classroom model) to a control group. The findings indicated a significant improvement in the reading comprehension skills of students in the experimental group. The pre-test mean score for the experimental group was 60.8, which increased to 87.8 after the intervention. This suggests that the Flipped Classroom model can positively impact students' ability to understand and analyze narrative texts. While the model offers flexibility, allowing students to learn at their own pace and revisit the material as needed, challenges such as the need for access to mobile devices and internet connectivity may hinder its effectiveness for some students. Despite these limitations, the Flipped Classroom contributed to increased student engagement, improved communication, and a more interactive learning environment. This study highlights the potential benefits of the Flipped Classroom model in enhancing students' reading comprehension and suggests further exploration of its implementation in different educational contexts.